[OA022] T2 and T* relaxometry of benign and malignant lipomatous tumors. (August 2018) - Nikiforaki, Katerina; Manikis, Georgios C.; Lagoudaki, Eleni; Venianaki, Maria; Marias, Kostas; Bree, Eelco; Maris, Thomas G.; Karantanas, Apostolos
Abstract : Purpose: T2 relaxation constant has been established as an accurate biomarker from the early days of MRI for tissue or material identification as it expresses physical properties without dependence on the MR protocol used. T2 * expresses acceleration of T2 dephasing process by local field inhomogeneities that can be produced by paramagnetic blood products, i.e. deoxyhemoglobin, hemosiderin. Therefore, long R2 ′ = 1/T2 * − 1/T2 relaxation rates are found in tissues with low oxygenation and/or high oxygen consumption. The present is a study of T2 and R2 ′ for the differentiation between benign and malignant lipomatous tumors. Methods: 16 patients with lipomatous tumors underwent preoperatively MRI examination including T2/T2 * relaxometry protocol. T2 relaxometry data were acquired from a Multi Echo Spin Echo CPMG sequence with initial echo at 26.8 ms followed by 9 equidistant echoes (echo spacing 26.8 ms) to avoid spin coupling signal modulation. T2 * protocol comprised 4 opposed-phased echoes (TE: 2.38/7.18/12.0/16.82 ms) and 4 in-phase echoes (4.77/9.59/14.41/19.23 ms). Histologic examination of surgical specimen showed 4 benign lipomas (bl), 4 well differentiated liposarcomas (wdl, Histologic Specific Differentiation Score (HSDS) 1), 2 non round cell myxoid liposarcomas (intermediately differentiated sarcomas, idl, HSDS 2) and 6 poorly differentiated liposarcomas (pdl, HSDS 3). 3D ROI based measurements were performed on areas indicated from histopathologic analysis as indicative of histologic subtype. Results: Average T2 (SD) constant for bl/wdl/idl/pdl is 102.2 (1.6)/101.9 (6.7)/562.55 (120.1)/131.8 (12.1) ms. R2 ′ for bl/wdl/idl/pdl is 23.1 (1.1)/17.2 (9.3)/1.6 (0.5)/4.6 (1.0) ms −1 . Similar metrics were taken on healthy subcutaneous tissue to ensure protocol robustness on healthy tissue (Normal fat T2/R2 ′ range: 98.9–102.0 ms/24.2–25.9 ms −1 ). Conclusion: Average T2 differs significantly between lipomatous masses of variable differentiation score in a limited sample of benign and malignant lipomatous tumors. R2 ′ is larger for lipomas and well differentiated liposarcomas compared to intermediate or poorly differentiated liposarcomas suggesting lower oxygen supply/consumption of the lesion.